In Vitro Biocontrol Evaluation of Some Selected Trichoderma Strains against the Root Pathogen Fusarium oxysporum of Hot Pepper (Capsicum annum L.) in Bure Woreda, Ethiopia. (16th July 2022) - Girma, Abayeneh
Abstract : Capsicum annum L. is a major vegetable crop consumed worldwide as a spice, vegetable, pickle, condiment, and sauce. Each year in Ethiopia, 80% of the yield loss of hot peppers is caused by Fusarium wilt. Controlling this disease using fungicides can pollute the environment and induce genetic resistance in fungal phytopathogens. To solve this serious problem, it is necessary to look for economically safe, long-lasting, and effective biocontrol alternatives. Therefore, the objective of this work was to evaluate antagonistically active Trichoderma strains against F . oxysporum f.sp.capsici using a dual culture assay. The results of this study revealed that out of 32 Trichoderma isolates tested in vitro, only six ( T . harzianum (TD1), T . asperellum (TD5), T . viride (TD7), T . hamatum (TD11), T . virens (TD15), and T . longibrachiatum (TD21)) strains showed a varying rate (45.72–93.57%) of biocontrol activity toward the tested pathogen. Of six isolates, three (TD5, TD1, and TD7) strains showed effective antagonists against the root pathogen Fusarium oxysporum f.sp.capsici of hot pepper ( C . annum ) with a colonization percentage of 89.45%, 90.12%, and 93.57%, respectively. These Trichoderma strains showed higher inhibition efficiency (> 70%) against the mycelial growth of F . oxysporum with good stress tolerance (temperature, pH, salt concentration, and heavy metals) ability. The isolates also produce different hydrolytic enzymes (amylase, protease, cellulase, and chitinase) with mycoparasitism potential against the mycelia growth of F . oxysporum . Therefore, the results of this study concluded that TD1, TD5, and TD7 Trichoderma strains showed potential biocontrol effects with wide stress tolerance ability against the root pathogen F . oxysporum of hot pepper and can thus be recommended as the best alternative for wide greenhouse and field trial evaluations.